Antenatal management of congenital diaphragmatic hernia: What's next ?. (14th March 2022) - Russo, Francesca; Benachi, Alexandra; Gratacos, Eduard; Zani, Augusto; Keijzer, Richard; Partridge, Emily; Sananes, Nicolas; De Coppi, Paolo; Aertsen, Michael; Nicolaides, Kypros H.; Deprest, Jan
Abstract: Congenital diaphragmatic hernia can be diagnosed in the prenatal period and its severity can be measured by fetal imaging. There is now level I evidence that, in selected cases, Fetoscopic Endoluminal Tracheal Occlusion with a balloon increases survival to discharge from the neonatal unit as well as the risk for prematurity. Both effects are dependent on the time point of tracheal occlusion. Fetoscopic Endoluminal Tracheal Occlusion may also lead to iatrogenic death when the balloon cannot be timely retrieved. The implementation of the findings from our clinical studies, may also vary based on local conditions. These may be different in terms of available skill set, access to fetal therapy, as well as outcome based on local neonatal management. We encourage prior benchmarking of local outcomes with optimal postnatal management, based on large enough numbers and using identical criteria as in the recent trials. We propose to work further on prenatal prediction methods, and the improvement of fetal intervention. In this manuscript, we describe a research agenda from a fetal medicine perspective. This research should be in parallel with innovation in neonatal and pediatric (surgical) management of this condition. Key points: What is already known about this topic ? Congenital diaphragmatic hernia (CDH) can be diagnosed and its severity assessed in the prenatal period. In fetuses with severe or moderate pulmonary hypoplasia, fetal surgery can be offered. In selected cases, Fetoscopic Endoluminal Tracheal Occlusion (FETO) improves survival but increases the risk for prematurity. What does this study add? Further research into accurate prenatal prediction of outcome is needed and the best biomarkers should be identified. We propose prospective registration of cases treated with FETO, to increase our understanding of the effect of the duration of occlusion and the potential impact of preterm delivery. Outcomes of fetal surgery should improve further, both by technical innovation in the current technique as well as the introduction of additional and more effective therapies.